Analisis Permasalahan Kepala Sekolah dalam Implementasi Kurikulum Merdeka di SD Negeri 3 Karanganom - Rifqi Asiah; Revina Rahmawati; Ayuna Asri Nurrohmah; Yudi Prabowo; Nela Rofisian (CV. ITTC INDONESIA, 2024)
The background of this research is to find out the problems faced by school principals in implementing the independent curriculum in elementary schools. The independent curriculum focuses on developing the character and morals of students, and the independent curriculum is more flexible and gives educators the freedom to develop learning according to the needs of students. Various challenges are faced by principals and educators in implementing the independent curriculum in elementary schools. The research conducted aims to analyze the various problems faced by school principals in implementing the independent curriculum in elementary schools. This research uses descriptive qualitative methods, data collected using interview techniques using interview sheets. After the research, it was found that SD N 3 Karanganom had successfully implemented the independent curriculum amidst the challenges.